Physiotherapy management of first nations children with bronchiectasis from remote top end communities of the northern territory: a retrospective chart audit - A Welford; GB McCallum; M Hodson; H Johnston (Frontiers Media S.A., 2023)
BackgroundBronchiectasis is a chronic pulmonary disorder which is prevalent among Australian First Nations people in the Northern Territory (NT). Current guidelines recommend physiotherapy as part of multi-disciplinary management of children with bronchiectasis, however in our setting, involvement of physiotherapy remains unknown. We thus undertook a retrospective chart audit to examine physiotherapy management of First Nations children (<18 years) from remote First Nations communities in the Top End of the NT at the index bronchiectasis diagnosis and 12 months following diagnosis.MethodsParticipants were identified from a larger prospective study of children investigated for bronchiectasis at Royal Darwin Hospital, NT (2007-2016). Children were included if they were First Nations, aged <18 years, had a radiological diagnosis of bronchiectasis on high resolution computed tomography scan and lived in a remote community serviced by NT Government health clinics. The medical records from NT Government hospitals, health clinics and where possible other medical service attendance were reviewed for physiotherapy referral and management at the time of bronchiectasis diagnosis and in the following 12 months in the community.ResultsOf 143 children included, the mean age was 3.1 (standard deviation 2.4) years and 84 (58.7%) were males. At the index diagnosis, 76/122 (62.3%) children were reviewed by a physiotherapist, consisting of airway clearance techniques (83.8%), physical activity/exercise (81.7%) and caregiver education (83.3%), with only 7/127 (5.5%) having evidence of referral for community-based physiotherapy. In the following 12 months, only 11/143 (7.7%) children were reviewed by a physiotherapist, consisting of airway clearance techniques (54.5%), physical activity/exercise (45.5%) and caregiver education (36.4%).ConclusionThis study demonstrates a significant gap in the provision of physiotherapy services in our setting and the need to develop a standardized pathway, to support the best practice management of children with bronchiectasis in remote Top End communities of the NT.